PKM PADA KELOMPOK PENGAJIAN HIDAYATULLAH DAN KELOMPOK PENGAJIAN AL IHLAS RW.17 SUDIMORO, KEL.MOJOLANGU,KEC.LOWOKWARU KOTA MALANG - Joko Samboro; Fadloli Fadloli; Sugeng Basuki; Sarjiyana Sarjiyana (Publisher UPT P2M Politeknik Negeri Malang, 2019)
The purpose of this Community Service is to find the problems faced by the Hidayatullah Group RT.7.RW.17 and the Al Ihlas Group RT.3.RW.17 and at the same time provide appropriate solutions to improve knowledge and capabilities in the operational sector especially the field of entrepreneurship, which starts since before doing activities, with aspects of intentions in entrepreneurship, then during conducting activities, namely in terms of the importance of ethical ethics in entrepreneurship and also given examples of the character of the Prophet Muhammad in trading, quality of service and also selling techniques, which ending with an agreement or better known as a deal and marked with a handshake, so that work does not only benefit, but also gets blessings. Thus this activity can improve the skills of both soft skills and hard skills members. Besides that, the achievement of a sense of peace, comfort and peace in the community was also achieved through the provision of a wheelbarrow (corpse coffin) and the procurement of sacrificial slaughterhouses.The method used is: observation, to observe the activities carried out both in the economic and social fields of religion, then interviews, were explored to find problems and solutions to be offered and simulations, to find the most appropriate alternative for marketing goods to be more effective.An overview of the technology to be applied.1. In the form of lectures: Group participants gathered in a particular room are given lectures on devotion material in the form of, ethics-based entrepreneurship, then handling corpses, making sacrificial animal slaughter tools.2. Guidance and Training: In the form of guidance and training on: entrepreneurship based on practical moral ethics and discussion of experiences and obstacles in the field.3. Simulation practice: In the form of a demonstration of how entrepreneurs offer goods, and how to attract potential customers, until the formation of closing / sales realization and how to handle the body, how to make a qurban slaughter tool,4. The practice of building a coffin and sacrificial slaughter tools